Complex conductivity of soils. Issue 8 (18th August 2017) - Revil, A.; Coperey, A.; Shao, Z.; Florsch, N.; Fabricius, I. L.; Deng, Y.; Delsman, J. R.; Pauw, P. S.; Karaoulis, M.; de Louw, P. G. B.; van Baaren, E. S.; Dabekaussen, W.; et al.
Abstract: The complex conductivity of soils remains poorly known despite the growing importance of this method in hydrogeophysics. In order to fill this gap of knowledge, we investigate the complex conductivity of 71 soils samples (including four peat samples) and one clean sand in the frequency range 0.1 Hz to 45 kHz. The soil samples are saturated with six different NaCl brines with conductivities (0.031, 0.53, 1.15, 5.7, 14.7, and 22 S m −1, NaCl, 25°C) in order to determine their intrinsic formation factor and surface conductivity. This data set is used to test the predictions of the dynamic Stern polarization model of porous media in terms of relationship between the quadrature conductivity and the surface conductivity. We also investigate the relationship between the normalized chargeability (the difference of in‐phase conductivity between two frequencies) and the quadrature conductivity at the geometric mean frequency. This data set confirms the relationships between the surface conductivity, the quadrature conductivity, and the normalized chargeability. The normalized chargeability depends linearly on the cation exchange capacity and specific surface area while the chargeability shows no dependence on these parameters. These new data and the dynamic Stern layer polarization model are observed to be mutually consistent. Traditionally, in hydrogeophysics, surface conductivity is neglected in the analysis of resistivity data. The relationships we have developed can be used in field conditions to avoid neglecting surface conductivity in the interpretation of DC resistivity tomograms. We also investigate the effects of temperature and saturation and, here again, the dynamic Stern layer predictions and the experimental observations are mutually consistent. Plain Language Summary: Geophysical methods are increasingly popular in agriculture. Usually, DC (DIrect Current) resistivity is the preferred method but the interpretation of resistivity data suffers a major flaw: the inability to distinguish between bulk and surface conductivity. This has yield to unrealistc interpretation schemes in hydrogeophysics and an abuse of Archie's law. We propose a way to cure this flaw by extending the DC resistivity method to what is called induced polarization. This paper is the first work entirely focused on the study of induced polarization of soils including a comparison with a mechanistic model and a study of the influence of both temperature and saturation. Key Points: A large data set of complex conductivity data on soils is presented Complex conductivity data are explained to the light of the dynamic Stern layer model Surface conductivity is related to the normalized chargeability or quadrature conductivity, which opens new perspectives in hydrogeophysics